Accommodation and the Strongest Meaning Hypothesis - Mayr, Clemens; Sauerland, Uli (Proceedings of the Amsterdam Colloquium, 2015)
Quantifiers have been claimed to differ with respect to how they project presuppositions from their scope. Early work claimed that, while negative quantifiers project presuppositions universally, indefinites do so existentially. But the environment the quantifier occurs in matters as well (e.g. Fox [12]). This paper suggests a new account of presupposition projection from a quantifier scope. We propose that, despite appearances, presupposition projection from the scope of quantifiers is always universal following Heim [16]. Apparent deviations from universal projection, we explain by means of additional acontextual silent restriction of quantifiers. Specifically, the mechanism of intermediate accommodation can add the presupposition of a quantifier’s scope to its restriction and thereby derive apparent existential projection. We propose furthermore that intermediate accommodation must be licensed by a version of the Strongest Meaning Hypothesis. Our account explains how the monotonicity properties of quantifiers and the environments they occur in determine their projection properties.